MINAT BELAJAR SISWA DALAM MENINGKATKAN KECERDASAN INTELEKTUAL SISWA SD NEGERI WILAYAH KABUPATEN PANDEGLANG - E. Nita Prianti; Khristina Sri Prihatin (Pro Patria: Jurnal Pendidikan, Kewarganegaraan, Hukum, Sosial, dan Politik, 2020)
Based on the fact that there is no end to the problems of education that occur in our country even though the government has worked hard to change it. The irrelevance between expectations, the process and the results achieved in education. Thus there are certainly other factors, one of which is the willingness or interest of students towards learning. The purpose of this study is 1) To find out how much the students' willingness to learn in improving the intellectual intelligence of students of SD Negeri Pandeglang district. 2) To find out the factors and efforts to improve the intellectual intelligence of students of SD Negeri Pandeglang district. The method used in this research is descriptive method with a qualitative approach. While the data source was obtained through informants as research subjects using data collection techniques in library research and field research (research locations) by observing, documenting, interviewing guidelines for several informants namely students, teachers (SD) in the State of Pandeglang Regency. Then the data is analyzed correctly. The data obtained from the results of the study is that students 'interest in learning to improve students' intellectual intelligence in the area of ​​Pandeglang Regency cannot be categorized well. This can be proven from the findings of researchers that students of the SD Negeri Pandeglang Regency will their interest in learning only reach 50%. From 4 schools based on the results of research data, with a low willingness to learn so that 32.18% of students cannot read and write.